Structural and Electrochemical Investigation of FexSi1-x Thin Films in Li Cells. Issue 9 (20th July 2016) - Du, Zhijia; Dunlap, R. A.; Obrovac, M. N.
Abstract : Fex Si1-x thin films with 0 ≤ x ≤ 0.46 have been prepared by combinatorial sputtering and their electrochemical properties have been studied in Li half-cells. X-ray diffraction showed that all of the films had an amorphous structure. Mössbauer effect spectra suggest that Fe was diluted in amorphous Si for x ≤ 0.23 and inactive FeSi2 was formed with further increase in x. For x ≤ 0.23, all Si in the thin films was active toward lithiation/delithiation. At higher Fe contents, the capacity of Fe-Si thin films dropped rapidly and no capacity was observed for x greater than 0.33. The voltage curve of Si to become depressed during lithiation with increasing Fe content, which may be the result of stress induced between the active Si phase and inactive phases in the alloy. For alloys with x > 0.23, the formation of inactive FeSi2 removes active Si from the alloy and results in the lowering of the reversible capacity.